Propuestas de mejora en los procesos logísticos para la empresa Viajes Confort SAS ubicada en Bogotá (2024)
The general objective of the research is to improve the logistics processes of Viajes Confort SAS in Bogotá D.C. due to the importance of logistics efficiency in business success. Specific objectives are to review the literature on logistics processes, perform an organizational diagnosis to identify problems and design a detailed improvement plan.In order to optimize the management of resources, improve the coordination of logistics operations and increase customer satisfaction, the impact of the implemented proposals will be measured in terms of operational performance, logistics costs and customer satisfaction, where the research not only seeks to solve the problems of Viajes Confort SAS but also offers a framework that can be replicated in other companies in the sector.